(untitled) (Mustansiria Dental Journal, 2018)
Acrylic denture base is the part of the denture that rests on the foundation tissue & to which the teeth are attached. The main objective of this study was to determine the effect of different cleansers solution on the impact strength of heat cure acrylic resin. Thirty (30) rectangular shape samples from acrylic were prepared with dimension of (55 mm *10 mm *2.5 mm) length, width& thickness .The acrylic was fabricated in the same conventional way for construction base palate. All the specimens were examined by vernier before immersion in solution to check the size of each samples, the samples were divided into three group (A, B& C) each group contain ten samples. The samples in first group (A) were immersed in distilled water, the samples in second group (B) were immersed in peroxide solution, while the sample in the third group (C) were immersed in prepared cleanser solution (citric acid).After period of immersion (for 3 week & 15 minutes every day).Finally each samples rinsed by distilled water & cleaned thoroughly by apiece of cotton before testing. The impact strength was tested in chapy impact machine. The statistical analysis of the results showed that there was no statically significant difference in impact strength value among the testing groups. This means that the all cleanser solution that were used in this study had no effect on the impact strength